The Vacuolar Inositol Transporter BvINT1;1 Contributes to Raffinose Biosynthesis and Reactive Oxygen Species Scavenging During Cold Stress in Sugar Beet - Berg, Johannes; Rodrigues, Cristina Martins; Scheid, Claire; Pirrotte, Yana; Picco, Cristiana; Scholz-Starke, Joachim; Zierer, Wolfgang; Czarnecki, Olaf; Hackenberg, Dieter; Ludewig, Frank; Koch, Wolfgang; Neuhaus, H. Ekkehard; et al. (Plant Cell and Environment, 2025)
Despite a high sucrose accumulation in its taproot vacuoles, sugar beet (Beta vulgaris subsp. vulgaris) is sensitive to freezing. Earlier, a taproot-specific accumulation of raffinose was shown to have beneficial effects on the freezing tolerance of the plant. However, synthesis of raffinose and other oligosaccharides of the raffinose family depends on the availability of myo-inositol. Since inositol and inositol-metabolising enzymes reside in different organelles, functional inositol metabolism and raffinose synthesis depend on inositol transporters. We identified five homologues of putative inositol transporters in the sugar beet genome, two of which, BvINT1;1 and BvINT1;2, are localised at the tonoplast. Among these, only the transcript of BvINT1;1 is highly upregulated in sugar beet taproots under cold. BvINT1;1 exhibits a high transport specificity for inositol and sugar beet mutants lacking functional BvINT1;1 contain increased inositol levels, likely accumulating in the vacuole, and decreased raffinose contents under cold treatment. Due to the quenching capacity of raffinose for Reactive Oxygen Species (ROS), which accumulate under cold stress, bvint1;1 sugar beet plants show increased expression of both, ROS marker genes and detoxifying enzymes. Based on these findings, we conclude that the vacuolar inositol transporter BvINT1;1 is contributing to ROS-homoeostasis in the cold metabolism of sugar beet.
CRIS-Team Scopus Importer:2025-01-31
Keywords: cold stress; inositol; raffinose family oligosaccharides (RFO); reactive oxygen species (ROS); sugar beet; transport protein; vacuole